(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Oral health problem needs special attention around worldwide, including in Indonesia. This study analyzed factors related to oral health problems, including tooth-brushing behavior, dental visit, and public health centers with many dentistsin all provinces in Indonesia. In this study, the ecological approach was carried outusing secondary data from the Ministry of Health of the Republic of Indonesia in 2018.Data from 34 provinces in Indonesia regarding tooth brushing behavior, dental visit, and public health centers with a sufficient number of dentistswere analyzed against the proportion of oral health problems using crosstabulation. This study found that the ratio of oral health problems in Indonesia is in the moderate category andtooth brushing behavior, dental visit, and public health centers with many dentistsin all provinces. Thus, oral health promotion and preventionthrough increasing awareness of maintaining oral health and equal distribution of dentists must be carried out to establish healthy community behavior in all provinces in Indonesia.